REAKSI TRANSESTERIFIKASI MINYAK KACANG TANAH (Arahis hypogea. L) DAN METANOL DENGAN KATALIS KOH - Purwati Purwati; Hartiwi Diastuti (Universitas Jenderal Soedirman, 2007)
Oil and fat as part of lipid are taking an important role in food industry. There are soluble vitamins, like A, D, E and K, in oil and fat. Oil, that is a source of essential acid, is a high energy source. Oil and fat take a role to improve the shape and to give a taste. This experiment have been conducted to investigate the quantity of methyl ester that is produced from transesterification reactions of peanut seed oil with methanol using KOH as a catalyst and to analyze a kind of methyl ester that is produced using GCMS.We got 68% v/v product of transesterification and we knew for kinds of methyl ester those were produced from GCMS. They are methyl palmitic, methyl linoleic, methyl stearic, dan methyl 12-hydroxil-9-octadecaenoic.